Defining key questions for clinical practice guidelines: a novel approach for developing clinically relevant questions - Samantha Chakraborty; Bianca Brijnath; Jacinta Dermentzis; Danielle Mazza (BMC, 2020)
Abstract Background There is no standardised protocol for developing clinically relevant guideline questions. We aimed to create such a protocol and to apply it to developing a new guideline. Methods We reviewed international guideline manuals and, through consensus, combined steps for developing clinical questions to produce a best-practice protocol that incorporated qualitative research. The protocol was applied to develop clinical questions for a guideline for general practitioners. Results A best-practice protocol incorporating qualitative research was created. Using the protocol, we developed 10 clinical questions that spanned diagnosis, management and follow-up. Conclusions Guideline developers can apply this protocol to develop clinically relevant guideline questions.